2016
DOI: 10.1177/1049732316672645
|View full text |Cite
|
Sign up to set email alerts
|

An Intersectional Analysis of Women’s Experiences of Smoking-Related Stigma

Abstract: In this article, we explore how young women encounter and counter discourses of smoking-related stigma. Twenty-seven young Australian women, smokers and ex-smokers, took part in interviews. A sub-sample of 18 participants took photographs to document their smoking experience, and took part in a second interview. Data were analyzed through Foucauldian discourse analysis. Four discourses were identified: "smoking as stigmatized," "the smoking double standard," "smoking as lower class," and "smokers as bad mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Qualitative research methods can also be used to explore the relative experiences of different types of stigma. Recent qualitative intersectional studies have focused on stigma related to a variety of health conditions and behaviors, including HIV [2, 3, 53], tobacco use [54], and mental health [55], most commonly as they relate to racial identity, gender, socioeconomic status, and sexual orientation. While intersectionality theory has been used in studies with diverse qualitative methodologies, a recent HIV-related review found that intersectionality was rarely the central focus [56] (see [41, 55, 57] for exceptions).…”
Section: Measurement and Analytical Approaches For Intersectional Stigmamentioning
confidence: 99%
“…Qualitative research methods can also be used to explore the relative experiences of different types of stigma. Recent qualitative intersectional studies have focused on stigma related to a variety of health conditions and behaviors, including HIV [2, 3, 53], tobacco use [54], and mental health [55], most commonly as they relate to racial identity, gender, socioeconomic status, and sexual orientation. While intersectionality theory has been used in studies with diverse qualitative methodologies, a recent HIV-related review found that intersectionality was rarely the central focus [56] (see [41, 55, 57] for exceptions).…”
Section: Measurement and Analytical Approaches For Intersectional Stigmamentioning
confidence: 99%
“…Instead, the lack of female participants indicates that women who smoke may be particularly stigmatized. Indeed, women smokers perceive a "smoking double standard" where women's smoking is seen as less desirable and less acceptable than men's smoking (Triandafilidis, Ussher, Perz, & Huppatz, 2017, p. 1450). However, the two female participants (one e-cigarette user, one cigarette smoker) appeared to experience less tension resulting from their smoking, generally recounting fewer identity gaps than the males in the group.…”
Section: Limitationsmentioning
confidence: 99%
“…Feminist analyses of the medicalization of pregnancy and the surveillance of pregnant bodies have shown that in contemporary 'Western' contexts, pregnant women are positioned as responsible for their fetus' health (Lupton, 1999(Lupton, , 2012Warin, Zivkovic, Moore, & Davies, 2012). They are expected to modify their practices during pregnancy to protect the 'vulnerable' fetus from all potential risks and threats (Lupton, 1999(Lupton, , 2012 and are subjected to continuous public surveillance and critical gazes which challenge 'deviant' practices (Burton-Jeangros, 2011;Greene, Ion, Kwaramba, Lazarus, & Loutfy, 2017;Lupton, 1999Lupton, , 2012Parsons, Ismail, Amiel, & Forbes, 2014;Triandafilidis, Ussher, Perz, & Huppatz, 2016). The way in which PA practices during pregnancy are interpreted within these discourses of risk and maternal responsibility may vary.…”
Section: Introductionmentioning
confidence: 99%